A helicase-independent activity of eIF4A in promoting mRNA recruitment to the human ribosome - Masaaki Sokabe; Christopher S. Fraser (2017)
In the scanning model of translation initiation, the decoding site and latch of the 40S subunit must open to allow the recruitment and migration of messenger RNA (mRNA); however, the precise molecular details for how initiation factors regulate mRNA accommodation into the decoding site have not yet been elucidated. Eukaryotic initiation factor (eIF) 3j is a subunit of eIF3 that binds to the mRNA entry channel and A-site of the 40S subunit. Previous studies have shown that a reduced affinity of eIF3j for the 43S preinitiation complex (PIC) occurs on eIF4F-dependent mRNA recruitment. Because eIF3j and mRNA bind anticooperatively to the 43S PIC, reduced eIF3j affinity likely reflects a state of full accommodation of mRNA into the decoding site. Here, we have used a fluorescence-based anisotropy assay to quantitatively determine how initiation components coordinate their activities to reduce the affinity of eIF3j during the recruitment of mRNA to the 43S PIC. Unexpectedly, we show that a full reduction in eIF3j affinity for the 43S PIC requires an ATP-dependent, but unwinding-independent, activity of eIF4A. This result suggests that in addition to its helicase activity, eIF4A uses the free energy of ATP binding and hydrolysis as a regulatory switch to control the conformation of the 43S PIC during mRNA recruitment. Therefore, our results define eIF4A as a universal initiation factor in cap-dependent translation initiation that functions beyond its role in RNA unwinding.